Investment Climate in Kyrgyz Republic : Views of Foreign Investors - World Bank Group (World Bank, Washington, DC, 2016)
The World Bank Group’s investment climate project conducted a survey of foreign investors in the Kyrgyz Republic - both those currently operating and those that have terminated their operations for various reasons. The purpose of the survey was to assess selected aspects of the investment policy and legal environment in place in the Kyrgyz Republic, so as to determine whether the current regulations are investment-conducive or otherwise. The following aspects were studied as part of this survey: reasons for selecting a country for investing, ease of market entry, investor confidence, and protection in running a business, investor incentives and market exit. This report presents the analysis of the results of the survey. It consists of six sections, five of which discuss the results of each of the assessed aspects of the investment policy. The sixth section presents some demographics of the survey.